1995
DOI: 10.1089/aid.1995.11.1073
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Human Thymic Organ Culture Model for the Study of HIV Pathogenesis

Abstract: The development of effective therapies for the treatment of AIDS would be facilitated by a better understanding of HIV pathogenesis in vivo. While some aspects of pathogenesis may be assessed by standard tissue culture assays, in vivo animal models may provide clues to other aspects of HIV-mediated progression toward AIDS. Current animal models include primate models for the study of simian immunodeficiency virus (SIV) and HIV, SCID-hu and hu-PBL SCID mouse models for the study of HIV, and feline models for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 30 publications
3
38
0
Order By: Relevance
“…In a small proportion of HIV-1-infected children, the loss of both peripheral CD4 + and CD8 + T cells appears to result from severe loss of DP cells (14). Similar data have been obtained from SIV-infected macaques (9,15), HIV-1-infected SCID-hu mice (16)(17)(18), and HIV-1-or Nef-expressing fetal thymic organ cultures (19,20). Finally, in transgenic (Tg) mice expressing Nef under the regulation of various T cell-specific regulatory sequences, depletion of DP, CD4 + SP, and CD8 + SP thymocytes could be documented (21)(22)(23).…”
supporting
confidence: 68%
“…In a small proportion of HIV-1-infected children, the loss of both peripheral CD4 + and CD8 + T cells appears to result from severe loss of DP cells (14). Similar data have been obtained from SIV-infected macaques (9,15), HIV-1-infected SCID-hu mice (16)(17)(18), and HIV-1-or Nef-expressing fetal thymic organ cultures (19,20). Finally, in transgenic (Tg) mice expressing Nef under the regulation of various T cell-specific regulatory sequences, depletion of DP, CD4 + SP, and CD8 + SP thymocytes could be documented (21)(22)(23).…”
supporting
confidence: 68%
“…Foetal thymus organ culture is a method that maintains the three-dimensional architecture of thymus and its cellular composition and allows in vitro growth and differentiation of thymic lobes [Bonyhadi et al, 1995;Kecha et al, 2000;Brilot et al, 2004]. It has been reported that, like human foetal thymus organ cultures, murine foetal thymus organ cultures closely mimic physiological conditions and therefore provide a very appropriate in vitro model and a more rapid means for the study and manipulation of T-cell development compared with alternative in vivo approaches [Plum et al, 1995;Owens et al, 2005].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that, like human foetal thymus organ cultures, murine foetal thymus organ cultures closely mimic physiological conditions and therefore provide a very appropriate in vitro model and a more rapid means for the study and manipulation of T-cell development compared with alternative in vivo approaches [Plum et al, 1995;Owens et al, 2005]. However, foetal thymus organ cultures have not been used extensively to investigate the consequences of a virus infection, and most studies were performed with HIV and human tissue or chimeric human/mouse tissue [Bonyhadi et al, 1995;Greiner et al, 1996;Choudhary et al, 2005].…”
Section: Discussionmentioning
confidence: 99%
“…Fresh pediatric thymus tissue was dissected into pieces containing 3-6 million cells and cultured as described previously (23). The appropriate tissue fragments were treated with 1 pg/ml LIF (BDPharMingen) for 1 hour before infection.…”
Section: Methodsmentioning
confidence: 99%
“…Most importantly, our findings have significant therapeutic implications since progesterone, which can upregulate the positive LIF regulator IL-4, is commonly and safely administered to women with reduced fertility to increase the chances of implantation and term pregnancy. Progesterone has also been shown to be decreased in HIV-1-infected placenta (23), so progesterone therapy may also be important in order to restore critical hormonal levels in HIV-1-infected women.…”
mentioning
confidence: 99%